(untitled) (Heritage, 2023)
Тhis paper tackles researching the tragedy of revenge features in Shakespeare’s play Hamlet and Death and the dervish novel by Meša Selimović. This paper aims to demonstrate why the protagonists are (not) the heroes of the revenge tragedy. Thus, it strives to shed light on the similarities and differences between the two them emphasizing why the Serbian novel deviates from the revenge tragedy conventions simultaneously pointing out those in line with these conventions. It will focus on the two most significant tragedy hubs such as crime and revenge. Additionally, this research paper will explore the aspects of brutality, and bloody scenes in the novel proving it can also be interpreted in the light of revenge tragedy, given the elements of violence such as murder and bloodthirsty horsemen and horses. Also, it tries to highlight the turning point in Hamlet’s character that occurred due to it being divided between stoicism and the will of God (predestination).